Effectiveness during ball screens in elite basketball games - Gómez, M.-A.; Battaglia, O.; Lorenzo, A.; Lorenzo, J.; Jiménez, S.; Sampaio, J. (Journal of Sports Sciences, 2015)
Ball screens are one of the most frequently used tactical behaviour in elite basketball games. The aim of the present study was to identify their predictors of success related to time, space, players, and tasks performed. The sample was composed of 818 ball screens corresponding to 20 close games (mean differences in score of 3.1 ± 0.8 points) randomly selected from the playoff games of the Spanish Basketball League (2008-2011). Classification tree analysis (CHAID) was used to analyse which variable or combination of variables, better predicts effectiveness during ball screens. The main results allowed identifying interactions with dribbler actions after the screen and the orientation of the screen on the ball. The results showed no interaction with game quarter and quarter minute temporal-related variables in both analyses. The present findings allow improving coaches` strategic plans that involve selecting the most appropriate offensive approach when performing ball screens.